Developing Teachers with Global Capabilities: A Paradigm Shift in Teacher Education in Ghana - Jiang, Annan (Journal of Theory and Practice of Contemporary Education, 2023)
As is well known, quality and positive school outcomes depend on the abilities, sensitivities, and motivations of teachers, which collectively refer to teacher quality. The role of teachers in shaping society requires the government to prioritize the training of teachers. Regarding the relevance of archival materials, this study mainly relies on observation and secondary data sources to conduct content analysis on teacher training in Ghana. This study identified various factors that contribute to improving the quality of teachers, ultimately improving the quality of education. This includes quality assurance for teacher education, initial training for teachers, deployment processes, professional growth, compensation, and regulatory agencies that ensure standards and compliance. The article also found that low investment in teacher education, allowing non professional graduates to teach, and poor living and working conditions have hindered teachers from working in rural and impoverished areas; The lack of regular and continuous training for professional development and the lack of motivation among teachers are some of the reasons for the low quality of basic school education. The study proposes that teachers must strictly accept training from educational institutions, recruit teachers through competency orientation tests, strengthen curriculum reform, improve teachers' critical thinking ability, regularly carry out teacher development training, and stimulate the enthusiasm of those teachers who are sent to rural areas.